Benzoxazolone Carboxamides: Potent and Systemically Active Inhibitors of Intracellular Acid Ceramidase1. (13th November 2014) - Pizzirani, Daniela; Bach, Anders; Realini, Natalia; Armirotti, Andrea; Mengatto, Luisa; Bauer, Inga; Girotto, Stefania; Pagliuca, Chiara; De Vivo, Marco; Summa, Maria; Ribeiro, Alison; Piomelli, Daniele
Abstract The ceramides are a family of bioactive lipid‐derived messengers involved in the control of cellular senescence, inflammation, and apoptosis. Ceramide hydrolysis by acid ceramidase (AC) stops the biological activity of these substances and influences survival and function of normal and neoplastic cells. Because of its central role in the ceramide metabolism, AC may offer a novel molecular target in disorders with dysfunctional ceramide‐mediated signaling. Here, a class of benzoxazolone carboxamides is identified as the first potent and systemically active inhibitors of AC. Prototype members of this class inhibit AC with low nanomolar potency by covalent binding to the catalytic cysteine. Their metabolic stability and high in vivo efficacy suggest that these compounds may be used as probes to investigate the roles of ceramide in health and disease, and that this scaffold may represent a promising starting point for the development of novel therapeutic agents.